New directions in grammaticalization research - Smith, Andrew D. M.; Trousdale, Graeme, 1971-; Waltereit, Richard (Studies in language companion series, 2015)
By arguing that grammaticalisation inevitably involves paradigmatisation, i.e. formation of new paradigms or reformation of existing paradigms, we challenge leading approaches to grammaticalisation that consider the stages on the so-called cline of grammaticality the prototypical path of grammaticalisation. After having questioned the notions of scalarity and gradualness, we present our concept of the grammatical paradigm and demonstrate the value of this concept in a discussion of examples from Polish, Russian, Danish, Italian and Finnish. The examples show that paradigmatic organisation is not restricted to morphology, but is also characteristic of word order and constructional syntax. Articles by prominent contributors to The Oxford Handbook of Grammaticalization (2011) are discussed during the presentation.